2020
DOI: 10.3390/cryst10100887
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Expansion of MgTiO3 Made by Sol-Gel Technique at Temperature Range 25–890 °C

Abstract: MgTiO3 is a material commonly used in the industry as capacitors and resistors. The high-temperature structure of MgTiO3 has been reported only for materials synthesized by the solid-state method. This study deals with MgTiO3 formed at low temperatures by the sol-gel synthesis technique. Co-precipitated xerogel precursors of nanocrystalline magnesium titanates, with Mg:Ti ratio near 1:1, were subjected to thermal treatment at 1200 °C for 5 h in air. A sample with fine powders of MgTiO3 (geikielite) as a major … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…2 shows that volume expansion is sensitive to the average Grüneisen parameter. In particular, the curve shows that the average value for the Grüneisen parameter, between 0.9 and 1.3, derived from the optic modes established by Raman spectroscopic measurements of Okada et al (2008) and Reynard and Guyot (1994) is too small to explain the volume expansion measured by Henderson (2009;Tuval et al 2020) and Zabicky et al 2009). These volume expansion data can only be explained by an average Grüneisen parameter of about 1.4.…”
Section: Mgtio 3 (Geikielite)mentioning
confidence: 99%
See 4 more Smart Citations
“…2 shows that volume expansion is sensitive to the average Grüneisen parameter. In particular, the curve shows that the average value for the Grüneisen parameter, between 0.9 and 1.3, derived from the optic modes established by Raman spectroscopic measurements of Okada et al (2008) and Reynard and Guyot (1994) is too small to explain the volume expansion measured by Henderson (2009;Tuval et al 2020) and Zabicky et al 2009). These volume expansion data can only be explained by an average Grüneisen parameter of about 1.4.…”
Section: Mgtio 3 (Geikielite)mentioning
confidence: 99%
“…based on a mixture of 95 wt% MgTiO 3 and 5 wt% Mg 2 TiO 4 (qandilite). According to Shindo (1980) and Wechsler and Navrotsky (1984), MgTiO 3 is a non-stoichiometric compound, which is able to dissolve a small excess quantity of Ti, but not Mg. Tuval et al (2020) showed experimentally and with the help of the phase diagram of MgO-TiO 2 published by Shindo (1980), that their sample contains MgTiO 3 near the stoichiometric composition, whereas the sample of Henderson et al (2009) most likely contains an excess of Ti, which explains the difference between the available V-T data sets. The V-T data set of Zabicky et al (2009) is consistent with that of Tuval et al (2020), because their sample is also a mixture of MgTiO 3 and Mg 2 TiO 4 .…”
Section: Mgtio 3 (Geikielite)mentioning
confidence: 99%
See 3 more Smart Citations